Waterhole - Bell, Fiona (University of Queensland Press, 2018)
A haunting and engaging debut from a talented Australian author. Sixteen-year-old Sunny Maguire is dreading the school holidays. She used to love visiting her grandmother's farm but ever since her mother died in a tragic car accident, Sunny doesn't feel at home anywhere anymore and the farm is a constant reminder of what she has lost. She knows it's going to be a long summer. Worse, she has to spend it with her distant stepfather, Kevin, the only ‘family' she has left. On her return to the small town of Kelly's Crossing, Sunny is distracted by a new resident – Matthew Bright – and the disappearance of local teenager Dylan Koslovski. She gets involved in the search for Dylan along the mysterious Constant Creek Gorge, a beautiful location tainted by tragic drownings. Complications arise when Kevin becomes a suspect in the case and rumours begin to circulate. Sunny doesn't trust him and she's beginning to lose faith in herself, too, especially when she starts to see her mother's ghost.